A Preliminary Analysis of Energy Consumption in Academic Buildings - Dzulkifly S.; Cheong Hou Y.; Aris H.; Hashim W.; Jorgensen B.N. (IOP Publishing Ltd, 2023)
Atmospheric temperature; Covariance matrix; Electric power utilization; Energy conservation; Office buildings; Space heating; Building energy consumption; Commercial building; Commercial energy; Electricity-consumption; Environmental issues; Outdoor temperature; Preliminary analysis; Technological advancement; Energy utilization